Municipal police and organized crime. The case of Michoacán, México - Ochoa, Jerjes Aguirre; Herrera Torres, Hugo Amador (REVISTA QUAESTIO IURIS, 2020)
This article analyzes the functions performed by municipal police to contain criminal activity in the state of Michoacán, Mexico; specifically in the ‘Hotlands’ (Tierra Caliente) in the 2000-2017 period. Using an ethnographic approach based on 35 in-depth interviews with key figures at the municipal level, we found that the police have been unable to control the advance of criminal activity. To make matters worse, there are cases in which they have become allies of delinquent groups. The lack of legitimacy of the police explains to a large extent their inefficiency. The study suggests that the only way out of the crisis of legitimacy facing municipal police forces is to strengthen the rule-of-law, consolidate democratic structures, and have the police adopt the role of mediators in social conflicts. Implementing structural solutions designed to improve the functioning of police in Mexico also demands enhancing the quality of the country’s democracy at the municipal level.